UPAYA PENINGKATAN KETERAMPILAN PRESENTASI PADA PEMBELAJARAN USHUL FIKIH MAHASISWA EKONOMI SYARIAH - Achmad Sholich; M. Maimun Haki Al Arif; Ahmad Khoirul Mustamir (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to enhance the presentation skills of Islamic Economics students in Ushul Fiqh learning through the implementation of systematically designed active-learning strategies. Presentation skills are essential for Islamic Economics students as they relate to the ability to construct arguments, communicate ideas logically, and present information professionally—competencies required in both academic contexts and the professional field. However, preliminary observations indicated that students often faced difficulties in organizing their presentation flow, using appropriate academic language, and connecting Ushul Fiqh concepts with Islamic economics contexts accurately. Responding to these challenges, this research employed a descriptive-qualitative approach that integrated presentation training, simulations, feedback sessions, and the use of standardized rubrics within the learning process. Data were collected through observation, documentation, video recordings of presentations, and student reflections. The findings revealed a significant improvement in students’ presentation structure, clarity of argumentation, mastery of content, media usage, and self-confidence. Students became more capable of explaining qawa'id fiqhiyyah, methods of istinbath, and their relevance to Islamic economic practices in a coherent and convincing manner. The learning approach, which positioned students as active participants, created a more interactive classroom environment and fostered critical thinking skills. Overall, the study concludes that presentation-based learning strategies, when organized through structured stages, are effective in improving both the conceptual understanding of Ushul Fiqh and the communicative competencies of Islamic Economics students.